Low-temperature giant coercivity in Co6.2Ga3.8−x Ge x (x = 2.4 to 3.2) - Jiro Kitagawa; Himawari Nomura; Terukazu Nishizaki (Materials Research Express, 2023)
The observation of giant coercivity exceeding 20 kOe at low temperatures in several transition-metal-based compounds has attracted significant attention from a fundamental perspective. This research is also relevant to developing rare-earth-free permanent magnets, wherein cobalt is one of the primary elements used. To facilitate easy fabrication, rare-earth-free and Co-based inorganic bulk magnets that exhibit giant coercivity are highly demanded but rarely reported. Herein, we report the observation of low-temperature giant coercivity in polycrystalline metallic Co _6.2 Ga _3.8− _x Ge _x ( x = 2.4 to 3.2) with the hexagonal Fe _13 Ge _8 -type structure composed of Kagome and triangular lattices. As the Ge content x decreases from 3.2, the magnetic ground state changes from ferrimagnetism to ferromagnetism at x = 2.6. In the ferrimagnetic state, we observed a signature of spin frustration arising from the Kagome and/or triangular lattices of Co atoms. The ferromagnetic ordering temperatures for the x = 2.6 and 2.4 samples are 46 K and 60 K, respectively. The coercive fields rapidly increase upon cooling and reach values of 26 kOe and 44 kOe in the x = 2.6 and 2.4 samples, respectively, at 2 K.